2014
DOI: 10.1039/c4ee01066c
|View full text |Cite
|
Sign up to set email alerts
|

Titanium incorporation into hematite photoelectrodes: theoretical considerations and experimental observations

Abstract: A thorough literature review and the investigation by soft X-ray absorption spectroscopy at synchrotron facilities of Ti-Hematite photoelectrodes are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
128
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(134 citation statements)
references
References 111 publications
5
128
1
Order By: Relevance
“…the distance between Ti and surrounding O and Fe atoms are different from that of pure hematite (shorter Ti−O and longer Ti−Fe bonds). No Fe 2+ and Ti 3+ were observed at doping levels up to 17%, in agreement with other reports 67,81,82. The water oxidation improvement was attributed to the formation of cation vacancies and shift of the valence band, increased carrier concentration and diffusion length 83.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…the distance between Ti and surrounding O and Fe atoms are different from that of pure hematite (shorter Ti−O and longer Ti−Fe bonds). No Fe 2+ and Ti 3+ were observed at doping levels up to 17%, in agreement with other reports 67,81,82. The water oxidation improvement was attributed to the formation of cation vacancies and shift of the valence band, increased carrier concentration and diffusion length 83.…”
supporting
confidence: 88%
“…Structural parameters from the EXAFS simulations for undoped and Ti-doped samples indicated that Ti atoms substitute for Fe atoms and there is no evidence of interstitial Ti, in agreement with Kronawitter et al81 It was also found that Ti incorporation is associated with a slight site distortion, i.e. the distance between Ti and surrounding O and Fe atoms are different from that of pure hematite (shorter Ti−O and longer Ti−Fe bonds).…”
supporting
confidence: 80%
“…Hematite (α-Fe 2 O 3 ) is an earth abundant and low cost semiconductor that has been extensively studied as electrode material of electrochemical devices for energy conversion (e.g., photoelectrochemical water splitting and fuel cells) [1][2][3][4][5] and charge storage (e.g., electrochemical capacitors and Li-ion batteries). [6][7][8][9] However, several intrinsic properties of hematite hinder its applications in these electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…Such calculations, however, are for the moment rather far from routine. The same holds for calculations that aim to model the mobility of free charge carriers [137][138][139][140][141][142][143], which is a crucial property for good photoelectrodes but less relevant for polymeric and nanoparticulate systems where exciton dissociation occurs on the surface, and for calculations that explicitly study the electron/hole transfer between different sub-components of the photocatalyst and the photocatalyst and solution/surface species [99,144].…”
Section: Exciton Dissociation and Electron-hole Separationmentioning
confidence: 99%